Respostas

2014-06-13T19:44:10-03:00
3 sobre raiz de 2 + raiz de 5

      3
-------------------
√2 + √5


     3                  3(
√2-√5)                    3√2 - 3√5                          3√2 - 3√5
---------- =       -----------------------  = -----------------------------------------  = ------------------------=
√2 + √5        (√2 + √5)(√2-√5)        √2√2-√2√5 +√5√2 - √5√5        √2.2 + 0 - √5²


  3
√2 - 3√5                3√2 - 3√5         3√2 - 3√5        3√2 - 3√5 : 3      √2 - √5
------------------- =          --------------  =  -----------------=     ----------------   = -  ---------- =
    
√2² - √5²                  2 - 5                  - 3                 - 3          : 3       - 1


√2 + √5     então

Resposta = √5 - √2


  • Usuário do Brainly
2014-06-14T10:06:49-03:00
3/(√2 + √5)
3/√(2 + 5)
3/√7
3/√7 . √7/√7
(3 . √7)/(√7 . √7)
3√7/(√7)²
3√7/7